Calculated Entropies for n-Heptane, 2-Methylhexane, 2, 3-Dimethylpentane, and Radicals from the Loss of H Atoms. (18th June 2013) - Hudzik, Jason M.; Bozzelli, Joseph W.
Abstract : Entropy data are reported using different calculation methods for internal rotors on n -heptane, 2-methylhexane, and 2, 3-dimethylpentane and on the different radical sites of each species corresponding to the loss of a hydrogen atom for temperatures between 298 and 1500 K. Structures, moments of inertia, vibration frequencies, and internal rotor potentials are calculated at the B3LYP/6-31G(d, p) level of theory. Comparisons with experimental literature data suggest limitations inuse of the rigid-rotor harmonic-oscillator (HO) approximation and advantages to the use of internal rotation contributions for entropy relative to torsion frequencies. The comparisons suggest the need to include contributions from all internal rotors where the barriers are at or below those of the above molecules. Calculation of entropy from the use of internal rotor contributions provides acceptable approximations to available literature values. Entropy values for radicals corresponding to carbon sites on these hydrocarbons are presented.